2020
DOI: 10.32479/ijeep.10453
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Impact of Energy Imports, Fuel Substitution and Technological Change on Real Gdp: A Panel Data Study of Asean Countries

Abstract: The determinants of real GDP growth have been enticed the researchers and policy makers since the last century. This study aims to empirically analyze the role of efficient energy consumption in real GDP growth of ASEAN countries. For this purpose, study used energy import, fuel substitution, and technological change as independent variables to explain their impact on dependent variable such as real GDP growth. The panel data of eight ASEAN countries including Indonesia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Green distribution or logistics has three main benefits: a better environment, economy and society (Piecyk and Bjorklund, 2015). Implementing green logistics in Southeast Asian countries, including Indonesia, impacts the circular economy (Torasa and Mekhum, 2020). Another study found that the application of green logistics in Indonesia impacts circular economy implementation (direct effect), leading to business sustainability (indirect effect) (Muafi and Sugarindra, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Green distribution or logistics has three main benefits: a better environment, economy and society (Piecyk and Bjorklund, 2015). Implementing green logistics in Southeast Asian countries, including Indonesia, impacts the circular economy (Torasa and Mekhum, 2020). Another study found that the application of green logistics in Indonesia impacts circular economy implementation (direct effect), leading to business sustainability (indirect effect) (Muafi and Sugarindra, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…GLS4: Green IT . GLS operations enhance green IT and communication, enabled by implemented CE practices (Luu, 2021b; Torasa & Mekhum, 2020). GLS5: Green transportation .…”
Section: Theoretical Development Research Framework and Associated Hy...mentioning
confidence: 99%
“…GLS6: Green manufacturing . GLS operations reinforce environmentally‐friendly manufacturing techniques, through the adoption of CE methods (Luu, 2021b; Torasa & Mekhum, 2020). GLS7: Green storage .…”
Section: Theoretical Development Research Framework and Associated Hy...mentioning
confidence: 99%
“…This research's purpose is to study the endogenous relationship between the logistics level and industrial and commercial liabilities in the supply chain system, to discover and explain the systematic problems of supply chain dynamics, and to make a valuable marginal contribution to the exploration of supply chain finance. Both subjects involved in this study have been the subject of academic attention and research, from the logistics-economic perspective, the links between the level of logistics and the growth in economy has become a common topic of discussion, some scholars have also explored the relationship with the recycling economy from the perspective of green logistic, these studies basically take a macro perspective and land on the economic theme [1][2][3]. In the supply chain-debt perspective, the main subjects of research are the SC-failure's influence of on debt-equity, the analysis of debt in the supply chain and other corporate, technical topics, focus mainly on the management of the science and efficiency of the problem [4][5].…”
Section: Introductionmentioning
confidence: 99%